Prognostic values of the clinicopathological characteristics and survival outcomes in micropapillary urothelial carcinoma of the bladder: A SEER database analysis. (11th June 2020) - Jin, Di; Jin, Kun; Qiu, Shi; Zhou, Xianghong; Yuan, Qiming; Yang, Lu; Wei, Qiang
Abstract: Purpose: To study prognostic values of the clinicopathological characteristics and survival outcomes in micropapillary urothelial carcinoma (MPUC) of the urinary bladder. Method: We used the national Surveillance, Epidemiology, and End Results database (2004‐2016) to compare MPUC with transitional cell carcinoma (TCC) and to investigate prognostic values of clinicopathological characteristics, as well as survival outcomes, in MPUC of the urinary bladder. A multivariable Cox proportional hazard model, subgroup analyses, and propensity score matching were used. Results: In all, 519 patients with MPUC and 154 453 patients with TCC were enrolled. Compared with TCC, patients with MPUC had a higher rate of muscle invasive disease ( P < .001), lymph node metastasis ( P < .001), and distal metastasis ( P < .001), as well as higher tumor grade ( P < .001). According to the survival analyses, the MPUC group also had lower survival probability in both cancer‐specific mortality (CSM) ( P < .0001) and overall mortality (OM) analyses ( P < .0001). Cox proportional hazard regression showed that the MPUC group had a higher risk of OM (hazard ratios [HR] = 1.39, 95% confidence intervals [CI] = 1.22‐1.57, P < .0001), although the CSM (HR = 1.18, 95% CI = 1.00‐1.40, P = .0505) in that group was fair. In the subgroup analysis, only MPUC patients without distal metastasis faced a higher risk of CSM (HR = 1.33, 95% CI = 1.101.61, P < .0001). Conclusions: Micropapillary urothelial carcinoma prognosis is poorer than that of TCC. Micropapillary urothelial carcinoma is an independent prognostic factor for OM in patients with urinary bladder cancer. Abstract : The prognosis of micropapillary urothelial carcinoma (MPUC) is poorer than transitional cell carcinoma. Micropapillary urothelial carcinoma is an independent prognostic factor for overall mortality to patients with urinary bladder cancer. In subgroup analysis, only none distal metastasis MPUC patients faced higher risk of cancer‐specific mortality.